1992
DOI: 10.1139/b92-216
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in tomato infected with tomato leaf curl virus, a whitefly-transmitted geminivirus

Abstract: The ultrastructural modifications in nucleus of tomato infected with tomato leaf curl virus (TLCV) included hypertrophy of the nucleolus, segregation of nucleolar components into discrete granular and fibrillar regions, appearance of electron-dense particles associated ribbon-like structures, and presence of virus particles as either loosely compacted or hexagonally close-packed symmetrical arrays. The virus particles were isometric, about 18–20 nm in diameter. In the lumen of sieve elements, virus particles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Both were restricted to the phloem, irrespective of the host. These findings are consistent with many tissue localization reports using manifold techniques for systemically infected leaves (3,4,42,43). Michelson et al (26) have observed TYLCV DNA in tissues other than phloem in the inoculated leaves of tomatoes, independently of whether the plants carried the Ty-1 TYLCV tolerance gene or not.…”
Section: Vol 78 2004 Tylcv and Tylcsv In Single Nuclei 10719supporting
confidence: 90%
“…Both were restricted to the phloem, irrespective of the host. These findings are consistent with many tissue localization reports using manifold techniques for systemically infected leaves (3,4,42,43). Michelson et al (26) have observed TYLCV DNA in tissues other than phloem in the inoculated leaves of tomatoes, independently of whether the plants carried the Ty-1 TYLCV tolerance gene or not.…”
Section: Vol 78 2004 Tylcv and Tylcsv In Single Nuclei 10719supporting
confidence: 90%
“…Host choice can be affected by leaf architecture and colour (Sippell et al. 1987), leaf pubescence (McAuslane 1996), cuticle thickness (Channarayappa et al. 1992) and metabolites that play a role as repellent or attractant (Chermenskaya et al.…”
Section: Discussionmentioning
confidence: 99%
“…The role of chloroplasts in the life cycle of plant DNA-viruses needs to be examined. In studies of cellular alterations induced by various geminiviruses in systemically infected plants, dramatic morphological changes in the ultrastructure of chloroplasts were identified, such as vesiculated entities, reduced starch and chlorophyll content, accumulation of fibrillar inclusions, virus-like particles, and vDNA within plastids (Esau, 1933; Jeske and Werz, 1978, 1980a,b; Schuchalter-Eicke and Jeske, 1983; Jeske and Schuchalter-Eicke, 1984; Jeske, 1986; Gröning et al, 1987, 1990; Rushing et al, 1987; Channarayappa et al, 1992). For AbMV it was shown that the severity of chloroplast structure remodeling was dependent on light intensity, and diurnal and seasonal conditions.…”
Section: Plastids and Stromules In Viral Infectionmentioning
confidence: 99%